Tanzania: państwo i społeczeństwo : (od kolonializmu do współczesności) - Bar, Joanna (Księgarnia Akademicka Publishing, 2020)
TANZANIA: THE STATE AND SOCIETY (FROM THE COLONIAL PERIOD UNTIL THE PRESENT DAY) The monograph is addressed to everyone interested in broadly understood African issues. In Poland, no monograph on the history of Tanzania has been published so far, covering both the colonial era and the period of more than half a century that has elapsed since it regained independence in 1961. Neither are there studies on contemporary conditions for the development of this country; the political system or changes in the social structure. Time distance already allows for making some summaries, at the same time enabling an attempt to assess the pace of state development, at least on the scale of East Africa. What is interesting is the fact that in the 1990s, with the end of the “Cold War” era, there were some similarities between the political transformation of post-socialist countries and the course of reforms in some African countries, which in previous decades adopted certain solutions of the socialist system, and at a similar time entered the path of deep political and economic reforms.